Stress hormone and circulating biomarker profile of apical ballooning syndrome (Takotsubo cardiomyopathy): insights into the clinical significance of B-type natriuretic peptide and troponin levels. Issue 17 (24th May 2009) - Madhavan, M; Borlaug, B A; Lerman, A; Rihal, C S; Prasad, A
Abstract : Objective: To evaluate the stress neurohumoral and cardiac biomarker profile of patients with apical ballooning syndrome (ABS). Methods: Plasma-free metanephrines, B-type natriuretic peptide (BNP), high sensitivity C-reactive protein (hsCRP) and troponin T, as well as 24-hour urine catecholamines, metanephrines and free cortisol were measured in 19 ABS and 10 ST-elevation myocardial infarction (STEMI) patients. Results: An antecedent stressful event was identified in 15 ABS patients. There were no differences in plasma normetanephrine (median 0.64 (IQ range 0.43–0.97) nmol/l vs 0.53 (0.32–0.77) nmol/l, p = 0.44), metanephrine (0.10 (0.10–0.22) nmol/l vs 0.16 (0.10–0.38) nmol/l, p = 0.29), or cortisol levels (16.0 (7.3–44.0) μg/dl vs 13.0 (10.5–23.5) μg/dl, p = 0.95) between ABS and STEMI patients. The 24-hour urine metanephrines, catecholamines and cortisol levels were normal in the majority of ABS patients. Troponin T levels were lower (0.62 (0.18–0.84) ng/ml vs 3.80 (2.04–6.57) ng/ml, p<0.001), but BNP levels were higher in ABS compared with STEMI (944 (650–2022) pg/ml vs 206 (140–669) pg/ml, p = 0.009). HsCRP was similarly elevated in the two groups (11.0 (5.1–110.8) mg/l and 24.3 (8.1–88.6) mg/l, p = 0.78). Conclusions: Catecholamine and cortisol levels were not elevated in our cohort of ABS, suggesting that routine measurement of these stress hormones is unlikely to be of diagnostic value in practice. In contrast to STEMI, ABS is characterised by a greater elevation in BNP and less myonecrosis.